P541 Real-life effectiveness of ustekinumab in inflammatory bowel disease patients with concomitant psoriasis or psoriatic arthritis: an IG-IBD study. (25th January 2019) - Pugliese, D; Daperno, M; Fiorino, G; Savarino, E; Mosso, E; Biancone, L; Testa, A; Sarpi, L; Cappello, M; Bodini, G; Caprioli, F; Festa, S; et al.
Abstract: Background: Ustekinumab has been licensed for treating psoriasis, psoriatic arthritis and Crohn's disease. Few data exist regarding the effectiveness of ustekinumab in inflammatory bowel disease (IBD) patients treated for concomitant dermatological or rheumatological conditions. This study aimed to describe the outcomes of IBD patients who received subcutaneous ustekinumab through a dermatological or rheumatological prescription. Methods: This multi-centre, retrospective study included all IBD patients who were started on subcutaneous ustekinumab for concomitant active psoriasis or psoriatic arthritis, irrespective of IBD activity. The primary endpoint was overall ustekinumab persistence, defined as the maintenance of therapy because of sustained clinical benefit for IBD. Results: Seventy IBD patients (64 Crohn's disease / 6 ulcerative colitis) were enrolled. Most patients (95.7%) had been previously exposed to anti-TNFα drugs. The median follow-up on ustekinumab therapy was 10.7 months (range, 1.4–67.3). Twelve patients (17.1%) withdrew the treatment after a median of 7.4 months (range, 0.9–23.8). The cumulative probability of maintaining ustekinumab treatment was 97.1% at 6 months and 77.1% at 12 months. Among the 56 patients with active IBD at baseline, 34 (60.7%) were in clinical remission at the last follow-up visit, and their cumulative probability of achieving IBD clinical remission was 84.7% and 63.9% at 6 and 12 months, respectively. Ustekinumab induced clinical remission of psoriasis or psoriatic arthritis in 37/45 (82.2%) and in 15/25 (60%) patients, respectively. Nine patients experienced an adverse event, but only two stopped ustekinumab. Conclusions: Subcutaneous ustekinumab had a good effectiveness profile for IBD patients treated for concomitant dermatological or rheumatological conditions.